Strengthening the Position of Expert Witness in Judicial Process - Amarini, Indriati; Kartikawati, Ratna (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2020)
An expert witness is a person requested to give testimony based on his/her specific expertise in a court trial. Expert testimony is needed to help the judges discovering the truth. A problem emerges when the expert witness is sued for his/her testimony by the losing party. The purpose of this research is to elaborate the role of expert witness and the need to strengthen its position in judicial process. This doctrinal research relies on the secondary data and employs a qualitative juridical analysis. The result of the research shows that the expert testimony is needed to clarify particular issue that cannot be addressed by the judges themselves. Considering its importance, the expert witnesses should be able to give their testimonies freely and protected from any legal action due to their testimonies.Â